2014
DOI: 10.1177/0218492314532278
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral axillary artery aneurysms after Bentall procedure in Marfan syndrome

Abstract: A man with Marfan syndrome underwent a Bentall procedure for annuloaortic ectasia and severe aortic regurgitation at 43 years of age. Twenty-eight years after the Bentall procedure, he developed bilateral axillary artery aneurysms (length × diameter: right: 80 × 39 mm; left: 103 × 45 mm). Aneurysmectomy and reconstruction of the axillary artery were performed using an artificial vascular graft. Histological examination revealed cystic medial necrosis. The postoperative course was uneventful, but long-term foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“… 3 ) Furthermore, a bilateral axillary aneurysm with Marfan syndrome is even rarer, and few studies have reported such cases. 4 , 5 ) Notably, our case did not exhibit an aneurysmal change in the right axillary artery, and the size of the artery was standard.…”
Section: Discussionmentioning
confidence: 62%
“… 3 ) Furthermore, a bilateral axillary aneurysm with Marfan syndrome is even rarer, and few studies have reported such cases. 4 , 5 ) Notably, our case did not exhibit an aneurysmal change in the right axillary artery, and the size of the artery was standard.…”
Section: Discussionmentioning
confidence: 62%
“…In the literature, axillary artery aneurysms are mostly unilateral. Bilateral axillary artery aneurysms were only reported in two Marfan syndrome patients [ 7 8 ]. However, thrombus in the aneurysmal lumen, which are used for differential diagnosis of atherosclerotic aneurysms, were not reported in either of the Marfan syndrome patients [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The largest aneurysm treated by an endovascular method was 3 × 5 cm in size. Surgery is preferred for larger and tortuous aneurysms [ 7 ]. We also opted for surgery in this case because the aneurysms were very large and tortuous.…”
Section: Discussionmentioning
confidence: 99%
“…52 Myocardial infarction and bacterial endocarditis are some cardiac causes of death. 54 In vascular system, there can be many types of defects in arterial wall including calcification. Rarely it shows axillary artery aneurysm.…”
Section: Cardio-vascular Systemmentioning
confidence: 99%
“…49 MFS and Proteus syndrome also share ventricular hypertrophy and dysfunction, 50,51,65 systolic and diastolic abnormality, 51,66 cardiac murmur, angina pectoris, congestive cardiac failure and myocardial infarction in common. 52,54,66 On the other hand, Proteus syndrome and Progeria both can cause thickening of myocardial septum, 59,65 cardiomyopathy, myocardial fibrosis and mass, 59,66 and abnormality in vascular endothelium. 33,63,67 Some other regular features of cardio-vascular system which are common in all these three mutations are discussed in the Table 2.…”
Section: Cardio-vascular Systemmentioning
confidence: 99%